Mediating Role of Resourcefulness in the Relationship Between Illness Uncertainty and Poststroke Depression - Liu, Jing; Wang, Hongxia; Lin, Beibei; Ning, Liuqiao; Liu, Danman; Li, Jufang (Frontiers in Psychology, 2022)
Objectives To examine the association between illness uncertainty, resourcefulness, and poststroke depression (PSD) and identifies whether stroke patients’ resourcefulness plays a mediating role in the relationship between illness uncertainty and PSD. Methods A cross-sectional study was conducted from September 2020 to April 2021. A convenience sample of 355 stroke patients was recruited. A general characteristic questionnaire, the Mishel Uncertainty in Illness Scale, the Resourcefulness Scale (RS), and the Patient Health Questionnaire-9 (PHQ-9) were used to obtain data. Descriptive analysis, Student’s t-test, Mann–Whitney U-test, chi-squared test, hierarchical regression analyses, Pearson correlation analysis, and mediation analysis with the PROCESS macro were used to analyze the data. Results Illness uncertainty, resourcefulness, and PSD were significantly related to each other. Resourcefulness partially mediated the relationship between illness uncertainty and PSD. Conclusion Illness uncertainty and resourcefulness were significantly associated with PSD, and resourcefulness played a mediating role between illness uncertainty and PSD. Interventions designed to reduce illness uncertainty and enhance resourcefulness may contribute to the prevention and improvement of PSD.